One pot synthesis, in silico study and evaluation of some novel flavonoids as potent topoisomerase II inhibitors. (15th May 2021) - Sarkate, Aniket P.; Dofe, Vidya S.; Tiwari, Shailee V.; Lokwani, Deepak K.; Karnik, Kshipra S.; Kamble, Darshana D.; Ansari, Mujahed H.S.H.; Dodamani, Suneel; Jalalpure, Sunil S.; Sangshetti, Jaiprakash N.; Azad, Rajaram; Burra, Prasad V.L.S.; et al.
Graphical abstract: Highlights: One pot method was employed for the synthesis of novel flavonoid derivatives. Seven synthesized compounds demonstrated an antiproliferative effect comparable to that of doxorubicin. Two synthesized compounds exhibited robust inhibition of enzyme topoisomerase-II. Docking studies revealed the binding of synthesized compounds in between DNA base pair at active site of enzyme. Abstract: A library of novel flavonoid derivatives with diverse heterocyclic groups was designed and efficiently synthesized. Structures of the newly synthesized compounds 4a-i and 8a-l have been characterized by 1 H NMR, 13 C NMR, MS and elemental analysis. Anticancer activities were evaluated against MCF-7, A549, HepG2 and MCF-10A by MTT based assay. Compared with the positive control Adriamycin, compounds 4a, 4b, 4c, 4d, 8d, 8e and 8j were found to be most active anti-proliferative compounds against human cancer cell line. We found that compounds 4a and 4c exhibited inhibition of enzyme topoisomerase II with IC50 values 10.28 and 12.38 μM, respectively. In silico docking study of synthesized compounds showed that compounds 4a and 4c have good binding affinity toward topoisomerase IIα enzyme and have placed in between DNA base pair at active site of enzyme. In silico ADME prediction results that flavonoid coumarin analogues 4a-i could be exploited as an oral drug candidate.